Rethinking Policyholder Rights in Mutual Insurance Enterprises - Angel Firstia Kresna; Dewa Gede Giri Santosa (International Journal of Society and Law, 2026)
Mutual insurance companies in Indonesia operate under a unique legal structure that is fundamentally different from shareholder-based insurance corporations. Rather than acting merely as consumers, policyholders in these organizations collectively serve as co-owners. This study analyzes the legal characteristics of mutual insurance enterprises and examines the implications of this dual status and contractual rights arising from insurance policies. Employing a normative legal methodology, this research uses statutory and case approaches to analyze key regulations, including Law No. 40 of 2014 on Insurance, Government Regulation No. 87 of 2019, and Financial Services Authority Regulation No. 7 of 2023, along with several Supreme Court decisions concerning disputes involving AJB Bumiputera 1912. The findings indicate that the mutual structure creates policyholders within a complex, dual legal relationship. Recent judicial interpretations tend to prioritize the mutuality principle by rejecting breach of contract claims against the enterprise itself and instead directing liability toward management through tort-based claims. While this approach reinforces the conceptual nature of mutual enterprises, it raises serious concerns about the practical effectiveness of legal protection for policyholders. The study concludes that the current normative ambiguity regarding the legal status of policyholders requires a more balanced framework that harmonizes the principle of mutuality with enforceable protections for policyholders.